Influenza infection induces alveolar macrophage dysfunction and thereby enables noninvasive Streptococcus pneumoniae to cause deadly pneumonia - Verma, Atul K (J Immunol, 2020)
Secondary S. pneumoniae infection is a significant cause of morbidity and mortality during influenza epidemics and pandemics. Multiple pathogenic mechanisms such as lung epithelial damage, and dysregulation of neutrophils and alveolar macrophages (AMs), have been suggested to contribute to the severity of disease. However, the fundamental reasons for influenza-induced susceptibility to secondary bacterial pneumonia remain unclear. Here we revisited these controversies over key pathogenic mechanisms in a lethal model of secondary bacterial pneumonia, with a S. pneumoniae strain that is innocuous to mice in the absence of influenza infection. Using a series of in vivo models, we demonstrate that rather than a systemic suppression of immune responses or neutrophil function, influenza infection activates IFN-γ receptor (IFN-γR) signaling and abrogates alveolar macrophage (AM)-dependent bacteria clearance, and thereby causes extreme susceptibility to pneumococcal infection. Importantly, using mice carrying conditional knockout of Ifngr1 gene in different myeloid cell subsets, we demonstrate that influenza-induced IFN-γR signaling in AMs impairs their antibacterial function, thereby enabling otherwise noninvasive S. pneumoniae to cause deadly pneumonia.